The abandonment defense in private antitrust conspiracy cases - HUNTER, Howard (Institutional Knowledge at Singapore Management University, 1975)
The current unsettled state of the American economy has caused considerable comment about the purposes and effectiveness of the federal antitrust laws as economic regulatory statutes. Among government enforcers, the debates have been particularly acerbic. Trade journals have printed conflicting comments by representatives of a number of government regulatory agencies. Certain government representatives suggest that the regulatory agencies themselves have caused the development of anticompetitive practices while other enforcers and commentators have suggested that more government regulation of competition, or the sanctioning of greater industry cooperation rather than competition, would be beneficial to the economy.